2010
DOI: 10.1016/j.joca.2010.02.003
|View full text |Cite
|
Sign up to set email alerts
|

A statistical model of shape and density of the proximal femur in relation to radiological and clinical OA of the hip

Abstract: Statistical modeling of the appearance captures the patterns of variation in projected femoral morphology as visible on DXA images. We showed that these descriptors of subtle aspects of shape and density of the hip contain information about clinical status which common radiological measures do not. The presented results warrant further careful study of the method as a monitoring tool in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 33 publications
3
53
1
Order By: Relevance
“…In a study of the proximal femur, Gregory et al (2007) reported that flatter femoral heads and shorter femoral necks are associated with OA. However, conflicting results are reported in other works (Lynch et al 2009;Waarsing et al 2010). In terms of fracture risk, it is understood that localised changes in femoral neck and trochanter morphology can have significant effects on fracture resistance (Yang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of the proximal femur, Gregory et al (2007) reported that flatter femoral heads and shorter femoral necks are associated with OA. However, conflicting results are reported in other works (Lynch et al 2009;Waarsing et al 2010). In terms of fracture risk, it is understood that localised changes in femoral neck and trochanter morphology can have significant effects on fracture resistance (Yang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Shape is routinely characterised using statistical shape models (SSMs), for which a training set of shapes is described in a correspondent manner, then decomposed into a mean shape and significant components of variation. The use of SSM for femurs can be categorised based on application: image segmentation (Ramme et al 2011); model reconstruction (Rajamani et al 2007; Barratt et al 2008;Baka et al 2011); finite element modelling (Bryan et al 2010) and pathology classification and prediction (Gregory et al 2007;Lynch et al 2009;Waarsing et al 2010). An exhaustive review of these works is beyond the scope of this article, but to the best of the authors' knowledge, all treat the femur (or the distal or proximal femur when focusing on the knee or hip joint) as a single object in the SSM.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond shape, population models can include internal femur architecture [17,20], correlations to fracture and disease risk [14,21], mechanical behaviour [22] and anthropological and anthropometric data [5]. These models allow the prediction of femoral structure from correlated data, or vice versa.…”
Section: Population Models and The Musculoskeletal Atlas Projectmentioning
confidence: 99%
“…Previous studies have proposed that the outcome parameters from active shape and appearance models (AAM) (Cootes et al, 2001), called modes, may include information on the rotational alignment of the femur in a 2D image (Waarsing et al, 2010). If this hypothesis is true, the modes could be used to predict the rotation of the femur.…”
Section: Introductionmentioning
confidence: 99%
“…If this hypothesis is true, the modes could be used to predict the rotation of the femur. Two-dimensional active appearance models have also been used for evaluation of the relation between osteoarthritis in hip and femoral shape deformations (Waarsing et al, 2010). However, the outcome of the 2D AAM may be affected by the misalignment of the femurs in the X-rays used to create the AAM.…”
Section: Introductionmentioning
confidence: 99%